TERRESTRIAL ELECTROMAGNETIC FILLING IN NONHOMOGENEOUS RADIO-ELECTRONIC ENVIRONMENT - V. I. Mordachev (Doklady Belorusskogo gosudarstvennogo universiteta informatiki i radioèlektroniki)
The analysis of the terrestrial electromagnetic filling in severe radio-electronic environment specified by heterogeneity of the composition of stationary and mobile radio-electronic devices (RED), specified by presence of RED with a directivity and randomness of electromagnetic radiation power, and also by heterogeneity of power criteria of electromagnetic safety for RED of various kinds is made. The equations defining the relationship of terrestrial electromagnetic filling in such radio-electronic environment with total intensity of an electromagnetic background, created by stationary and mobile RED at a terrestrial surface, and also with probability of excess of maximum permissible level by the sum of total intensity of electromagnetic field from stationary and mobile RED, and of intensity of an external electromagnetic background, are received.